Review of the IMF's Strategy on Overdue Financial Obligations. (Policy Papers; Policy Paper, 2009)
This paper reviews progress under the IMF's strengthened cooperative strategy on overdue financial obligations. Total arrears to the Fund declined by SDR 11 million, to SDR 1,327 million, since the last review. While Sudan's payments in excess of its new obligations falling due to the Fund accounted for the decline, arrears by Somalia and Zimbabwe increased further. The majority of the arrears to the Fund (85 percent) were to the General Resources Account (GRA).